Microencapsulation of ergosterol and Agaricus bisporus L. extracts by complex coacervation using whey protein and chitosan: Optimization study using response surface methodology - Rudke, Adenilson (2018)
In the present work microencapsulation was applied to an ergosterol enriched extract (EEE) from Agaricus bisporus L. and pure ergosterol (PE) using a complex coacervation process. The process was optimized following two steps: (i) using response surface methodology to optimize the conditions of temperature (T, 55 to 95 °C), protein-to-chitosan ratio (P/C, 0.5 to 10.5), maximizing yield (Y1, %, w/w), efficiency (Y2, %, w/w) and load (Y3, %, w/w); and (ii) using the dose-response methodology to optimize the ergosterol content (E) at the optimal conditions achieved in (i). The global optimal conditions for both cases were the same (T of 55 °C and a P/C of 0.5), but with maximized responses of Y1=75.02%; Y2=100.00%, Y3=12.78%, and Y1=19.19%; Y2=100.00%, Y3=15.87%, respectively. The effect of increasing ergosterol content led to the reduction of the microencapsulation yield, but with an increase in the ergosterol load and maintenance of the microencapsulation efficiency.